The Silicon Valley of dreams : environmental injustice, immigrant workers, and the high-tech global economy - Pellow, David N., 1969- (Critical America., 2002)
Next to the nuclear industry, the largest producer of contaminants in the air, land, and water is the electronics industry. Silicon Valley hosts the highest density of Superfund sites anywhere in the nation and leads the country in the number of temporary workers per capita and in workforce gender inequities. Silicon Valley offers a sobering illustration of environmental inequality and other problems that are increasingly linked to the globalization of the world's economies. In The Silicon Valley of Dreams, the authors take a hard look at the high-tech region of Silicon Valley to examine environmental racism within the context of immigrant patterns, labor markets, and the historical patterns of colonialism. One cannot understand Silicon Valley or the high-tech global economy in general, they contend, without also understanding the role people of color play in the labor force, working in the electronic industry's toxic environments. These toxic work environments produce chemical pollution that, in turn, disrupts the ecosystems of surrounding communities inhabited by people of color and immigrants. The authors trace the origins of this exploitation and provide a new understanding of the present-day struggles for occupational health and safety. The Silicon Valley of Dreams will be critical reading for students and scholars in ethnic studies, immigration, urban studies, gender studies, social movements, and the environment, as well as activists and policy-makers working to address the needs of workers, communities, and industry.